2016
DOI: 10.1111/dar.12436
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and factors associated with ever perpetrating intimate partner violence by men receiving substance use treatment in Brazil and England: A cross‐cultural comparison

Abstract: Introduction and Aims. Intimate partner violence (IPV) perpetration is common among men who use substances. Substance use is a contributing factor for IPV perpetration. This cross-sectional study determined lifetime prevalence and factors associated with ever perpetrating IPV by men receiving substance use treatment in Brazil (n = 281) and England (n = 223). Design and Methods. IPV, adverse childhood experiences, attitudes towards gender relations and roles, current health state, substance use, depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 86 publications
(130 reference statements)
3
62
0
7
Order By: Relevance
“…In both England and Brazil, participants in our study who were more supportive of gender equitable norms were less likely to report controlling behaviour. It is interesting that in spite of the higher support for gender equitable relations and less gender stereotyped attitudes in England compared to Brazil , the prevalence of perpetrating controlling behaviour was similar. While Stark's suggestion that physical IPV may be used to maintain ‘coercive control’ is partially supported in the Brazil data, the data from England suggests that more subtle forms of IPV, including TFA, may also be used to enforce control in a cultural context where male domination and IPV are less socially accepted.…”
Section: Discussionmentioning
confidence: 94%
“…In both England and Brazil, participants in our study who were more supportive of gender equitable norms were less likely to report controlling behaviour. It is interesting that in spite of the higher support for gender equitable relations and less gender stereotyped attitudes in England compared to Brazil , the prevalence of perpetrating controlling behaviour was similar. While Stark's suggestion that physical IPV may be used to maintain ‘coercive control’ is partially supported in the Brazil data, the data from England suggests that more subtle forms of IPV, including TFA, may also be used to enforce control in a cultural context where male domination and IPV are less socially accepted.…”
Section: Discussionmentioning
confidence: 94%
“…These can include mental health, medical, housing, unemployment, education and training needs, as well as issues with criminal justice and social services [24] and potentially intimate partner violence [5]. Unmet psychosocial needs can result in treatment drop out, highlighting the need for a holistic approach to treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in this special issue show how mixed methods studies across different countries can help disentangle the nuances of the phenomenon of IPV. While the quantitative data from studies by Gilchrist et al and Watt et al . suggested gender symmetry in the rates of IPV victimisation and perpetration experienced, their qualitative data provide a more nuanced contextual understanding, with instances of victimisation of women by male partners characterised as particularly frequent and intense.…”
mentioning
confidence: 99%
“…While IPV is prevalent in all cultures and countries [1], cultures where norms that justify wife beating and male control of female behaviour are widely held report higher rates of IPV [16]. In this issue, Gilchrist et al [17] compared the prevalence and risk factors for IPV perpetration among men in treatment for substance use in England and Brazil. They found that despite more genderstereotyped attitudes towards women and gender roles in Brazil, similar rates of emotional IPV were reported across the two countries, higher rates of sexual IPV perpetration were reported in Brazil and higher rates of physical IPV perpetration were reported in England.…”
mentioning
confidence: 99%